Hubungan Resiliensi Dengan Tingkat Kecemasan Pada Family Caregiver Lansia Dengan Komorbiditas Di Masa Pandemi COVID 19 - Duma Lumban Tobing; Karina Oktaviyadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
ABSTRACT Background: Resilience is a human ability to adapt in the face of sadness, and the constant and significant pressures in life. Resilience in the family during the COVID-19 pandemic has certainly experienced many changes due to significant changes. If the resilience process does not go well, the impact that will arise is that it can trigger anxiety. Objective: To determine the relationship between resilience and anxiety in elderly family caregivers with comorbidities during the COVID-19 pandemic. Methods: This study used a correlational design with a cross-sectional approach to determine the correlation between two variables, the independent variable resilience and the dependent variable anxiety of elderly family caregivers with comorbidities. Data collection was carried out through direct observation using the Connor Davidson Resilience Scale (CD-RISC) instrument and a questionnaire. Zung Self Rating Anxiety Scale (ZRAS). The sample in this study amounted to 85 respondents who were taken using a purposive sampling technique. The data analysis used was univariate and bivariate analysis using the chi-square test. Results: The data showed that 44 (51.8%) respondents had low levels of resilience and 44 (51.8%) respondents had moderate levels of anxiety. The results showed that there was a significant relationship between resilience and the anxiety level of elderly family caregivers with comorbidities with a p-value of 0.00 (p <0.05). Conclusion: There is a significant relationship between resilience and the anxiety level of elderly family caregivers with comorbidities. It is hoped that the family caregiver can form a self-help group that is used as a support group Keywords: COVID-19, Family Caregiver, Anxiety, Resilience